2013
DOI: 10.1063/1.4804280
|View full text |Cite
|
Sign up to set email alerts
|

Improved fluid simulations of radio-frequency plasmas using energy dependent ion mobilities

Abstract: Symmetric and asymmetric capacitively coupled radio-frequency plasmas in oxygen at 40 Pa, 300 V voltage amplitude and a discharge gap of 40 mm are investigated by means of one-dimensional numerical semi-kinetic fluid modeling on the basis of a simplified reaction scheme including the dominant positive and negative ions, background gas, and electrons. An improved treatment, by accounting for the dependence of ion mobilities on E/N, is compared to the standard approach, based on using zero-field mobility values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…In this work, a self-consistent one-dimensional (1D) fluid model, incorporating a semi-kinetic treatment of electrons and energy dependent ion mobilities is used [65]. The domain is a 1D slice of a typical geometrically symmetric CCP reactor with a discharge gap of 25mm, similar to various commercial and research systems [22,34,66].…”
Section: Numerical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, a self-consistent one-dimensional (1D) fluid model, incorporating a semi-kinetic treatment of electrons and energy dependent ion mobilities is used [65]. The domain is a 1D slice of a typical geometrically symmetric CCP reactor with a discharge gap of 25mm, similar to various commercial and research systems [22,34,66].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The domain is a 1D slice of a typical geometrically symmetric CCP reactor with a discharge gap of 25mm, similar to various commercial and research systems [22,34,66]. The simulation approach and governing equations are described in detail in [65]. Briefly, the simulation solves the mass and momentum (via the drift-diffusion approximation) conservation equations for electrons and ions.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing these cross-sections, the Monte-Carlo code described in the previous section yielded mobilities for the He + ions in a He gas under atmospheric pressure, which we approximated by the analytical fits listed in the Table II. A better fit can be made to match expected the high field asymptotics, µ ∝ E −0.5 (see the discussion in [18]), more accurately, yet we have found that the simple formula given in Table II gives a good agreement for E < 5 × 10 6 V/m, which is the range of the electric field values observed in the simulations. Similarly, the analytical fit for the momentum exchange frequency in the elastic scattering between He + ions and He atoms is listed in Table III.…”
Section: Validation Of the Hybrid Codementioning
confidence: 57%
“…A detailed description of the set of equations and associated conditions as utilized in this work can be found in Ref. 16 and the references therein.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%